1998
DOI: 10.1074/jbc.273.11.6550
|View full text |Cite
|
Sign up to set email alerts
|

Small Mechanical Strains Selectively Suppress Matrix Metalloproteinase-1 Expression by Human Vascular Smooth Muscle Cells

Abstract: Mechanical forces and biochemical stimuli may interact to regulate cellular responses. In this study, we tested the hypothesis that very small mechanical strains interact with growth factors in the regulation of matrix metalloproteinase (MMP)-1. Human vascular smooth muscle cells (VSMCs) were cultured on a precoated silicone membrane in a device that imposes a highly uniform biaxial strain. VSMCs cultured on fibronectin were treated with cyclic 1-Hz strains of 0, 1, or 4%, and MMPs were assayed by Western anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 42 publications
(30 reference statements)
1
39
0
Order By: Relevance
“…Whereas in another study, MMP-1 levels have been reported to be increased with cyclic stretching in human vascular smooth muscle cells (107). In other studies, relative MMP-2 levels were demonstrated to be altered as a function of the magnitude of cyclic strain and the duration of the strain (475,519). In a study by Garcia and colleagues (332), it was demonstrated that local alterations in myocardial strain in vivo could alter local MMP levels.…”
Section: Mechanical Stimuli and Mmp Transcriptionmentioning
confidence: 96%
See 1 more Smart Citation
“…Whereas in another study, MMP-1 levels have been reported to be increased with cyclic stretching in human vascular smooth muscle cells (107). In other studies, relative MMP-2 levels were demonstrated to be altered as a function of the magnitude of cyclic strain and the duration of the strain (475,519). In a study by Garcia and colleagues (332), it was demonstrated that local alterations in myocardial strain in vivo could alter local MMP levels.…”
Section: Mechanical Stimuli and Mmp Transcriptionmentioning
confidence: 96%
“…However, the relative degree of MMP induction is likely to be time and stimulus-type dependent. For example, a small uniform biaxial strain reduced MMP-1 expression in human vascular smooth muscle cells (519). Whereas in another study, MMP-1 levels have been reported to be increased with cyclic stretching in human vascular smooth muscle cells (107).…”
Section: Mechanical Stimuli and Mmp Transcriptionmentioning
confidence: 97%
“…fl-coll [3], as well as other signals that induce changes in cell morphology and actin reorganization, stimulate MMP-1 expression. The other signals include mechanical strain [4] and direct mechanical wounding [5] in human vascular smooth-muscle cells, exposure to cytochalasin D in human and rabbit synovial fibroblasts [6,7] and specific cell-matrix interactions [8].…”
Section: Introductionmentioning
confidence: 99%
“…These events include induction of several genes that may affect arterial extracellular matrix, including tenascin-C and plaminogen activator inhibitor-1. In addition, small deformations specifically suppress matrix metalloproteinase-1, an enzyme that can initiate degradation of fibrillar collagen (16).…”
mentioning
confidence: 99%